PENGARUH KADER TERHADAP PRAKTIK KESEHATAN IBU HAMIL PADA MASA PANDEMI COVID 19 - Heny Rosiana; Ana Sundari (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
Covid 19 is caused by SARS-COVID 19 virus. The virus is spread primarilfrom the nose or mouth from infected person to other person in close induce disorders on pregnancy, because of the change on physiology change on pregnancy, although its need more research to prove it. Cworkers or we called cadre is person who work in community and help information and motivation to pregnant women to be able practice hepregnancy during pandemic. This research is quantitative quasy experimenpre post design. The sample is 38 pregnant women on September to OPenanggulan and Pucangrejo, Pegandon, Kendal districts. The resulcommunity health worker is important and have significantly effect to practicing health protocol in pregnancy during pandemic (p value: 0,014). cadres have significantly effect to change behaviour of pregnant women practto prevent transmission of covid 19 virus.